Pro-inflammatory Cytokines and Oxidized Low-Density-Lipoprotein in Patients With Fibromyalgia - Funda Canpolat KUTU; Şenay ÖZDOLAP; Selda SARIKAYA (Archives of Rheumatology, 2019)
Objectives: This study aims to evaluate the differences in serum levels of tumor necrosis factor-alpha (TNF-α), interleukin-1 beta (IL-1β), (IL-8), and oxidized low-density lipoprotein (Ox-LDL) between female fibromyalgia (FM) patients and healthy females and also to examine a possible relationship between the cytokines/biomarker and the severity of pain and clinical features of FM. Patients and methods: This case-control study included 48 female patients (mean age 26.51±6.98 years; range, 18 to 50 years) who were diagnosed with FM according to the American College of Rheumatology criteria and 43 healthy female subjects (mean age 23.93±4.22 years; range, 18 to 50 years). Serum levels of TNF-α, IL-1β, IL-8, and Ox-LDL were measured by enzyme-linked immunosorbent assay in both groups. Fibromyalgia Impact Questionnaire, Visual Analog Scale, symptom severity scale, and widespread pain index were carried out and also their relationships with TNF-α, IL-1β, IL-8, and Ox-LDL levels were evaluated. Results: There was no difference in levels of the serum TNF-α, IL-1β, IL-8, and Ox-LDL between FM patients and healthy controls (p>0.05). The severity of pain was significantly associated with TNF-α (r=0.338; p=0.021) and IL-8 (r=0.299; p=0.043) levels, and Ox-LDL (r=0.415; p=0.006) level was found to be related to symptom severity of FM. Conclusion: Our results suggest that serum levels of TNF-α and IL-8 may be involved in the occurrence of pain in FM. The level of Ox-LDL may play an important role in the severity of symptoms. Future studies are needed to determine whether and how Ox-LDL plays a role in FM.